(untitled) (Journal of Hama University, 2024)
The aim of the research is to reveal the requirements of a safe school environment in the light of the school reform approach from the point of view of the principals of the first cycle schools of the basic education stage in the city of Damascus, as well as to reveal the differences between the average scores of the research sample members on the identification of the requirements of the safe school environment in the light of the school reform entrance. It is attributed to the research variables (Educational Qualification -Years of Experience) The research sample consisted of (85) principals from among the principals of the first cycle schools of basic education in the city of Damascus, they were chosen by a simple random method, the descriptive analytical method was used, and the questionnaire was used as a tool for data collection: 1-The requirements of a safe school environment came in light of the approach to school reform from the point of view of the principals of the first cycle schools of the basic education stage in the city of Damascus, ( the members of the research ) sample to a large extent, with an arithmetic mean of (75.3), and a percentage of (75%). 2- The order of the requirements of a safe school environment in light of the school reform approach came as follows: Administrative requirements ranked first with an arithmetic average of (04.4) and a percentage of (08.80%), followed by the physical requirements in the second place with an arithmetic average of ( 74.3 ) and a percentage of (8.74%), then in the third place are health requirements with an arithmetic average of (63.3) and a percentage of (6.72%), followed by in the fourth place are the legislative requirements with an arithmetic average of (58.3) and a percentage of (6,71%). 3-There are no statistically significant differences at the level of significance (0.05) between the averages of the answers of the members of the research sample to the questionnaire of the requirements of a safe school environment in the light of the school reform approach due to the research variables (scientific qualification - years of experience). 4-In light of the results reached, it is necessary to work to provide the requirements for a safe school environment in the schools of the first cycle of basic education in cooperation with the Ministry of Education and the school administration, and to pay attention to providing means of public safety in the school building.